Nuevos desafíos en los programas de control sanitario de ratones - Masselli Rodrigues-Demolin, Daniele (2021)
Rodent health monitoring program implemented in animal facilities is dynamic and has been in continuously progress. Laboratory animals can harbor infectious agents known to impact both animal welfare and biomedical research.